Peer-group mentoring for primary pre-service teachers during professional experience. Issue 3 (26th May 2020) - Cavanagh, Michael; King, Alexis
ABSTRACT: The purpose of this study is to explore the experiences of primary pre-service teachers engaged in a peer-group mentoring program during a professional experience placement. Pre-service teachers completed weekly questionnaires and an interview about their experiences. Questionnaire and interview responses were coded and analysed according to three domains of teacher development: professional, personal and social. Common themes about the participants' peer-group mentoring experiences include the role of the professional standards, the practical nature of the activities, increased confidence to teach and feelings of belonging and being supported. However, pre-service teachers did not make links between theory and practice in the sessions. This study provides insights into how the Finnish model of peer-group mentoring might be implemented for pre-service teachers in an Australian context.